The Effect of Different Carbon Sources on the Growth and Survival of Vanname Shrimp(Litopenaeus vannamei) with Biofloc Systems - Lubis, Muhammad Reza Idris; Rusliadi, Rusliadi; Putra, Iskandar (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT Vaname Shrimp (Litopenaeus vannamei) is one of the cultivation commodities that have high economic value and is classified as easier to cultivate because it is more resistant to disease attacks.. Biofloc technology is one of the right technologies for intensive maintenance of shrimp. The research was conducted on April – May 2018, at the Laboratory of Technical Services Unit Aquaculture of Technology, Faculty of Fisheries and Marine University of Riau. This study aims to understand the best type of carbon source for the growth and survival of vaname shrimp with biofloc systems. This study used a completely randomized design (CRD) of one factor consisting of four levels of treatment with three replications. The treatment used in the addition of different carbon sources are a) Without giving carbon (control), b) Adding carbon sources from molasses, c) Adding carbon sources from tapioca flour, and d) Adding carbon sources from sugar. The results show that the best treatment was the addition of carbon molasses (b) in the maintenance medium which resulted in an absolute weight growth of 1,77 grams, a specific growth rate of 13,20%, and a survival rate of 96,67%. Water quality parameters such as temperature in all treatments  25.8-28.3 oC, pH  7.3 to 8.1, dissolved oxygen 5.3 to 8.3 mg /L.Keyword :Litopenaeus vannamei., Carbon source, Bioflock System, Brackish water